Do we need the IMF to resolve a crisis? Lessons from past episodes of debt restructuring - Philipp Maier (Bank of Canada, 2007)
This study investigate how debt restructurings have evolved over the decades. Debtors and creditors have a long history of engaging an outsider a third party”, such as the IMF to organise and facilitate debt restructurings. As we show, the importance of these third parties” has grown over time. At the same time, the financial environment has evolved rapidly, and financial markets have become more liquid and better able to spread risk in recent decades. In today's economic environment, the financial system of many advanced countries is better isolated from the negative consequences of a lengthy restructuring process. Consequently, from the perspective of creditor countries, the fact that third parties” can facilitate and shorten the restructuring process has become less valuable. That said, emerging economies still benefit from involving a third party”, as this might help to overcome coordination problems among creditors and signal that the local authorities are effectively dealing with the crisis, which might help to restore confidence. This holds all the more since creditors have better access to litigation nowadays than during earlier episodes of debt restructurings.
Keywords: N1; N2; E5; F3; 330; Financial stability; International topics; Finanzmarktkrise; Auslandsverschuldung; Schuldenerlass; Finanzgeschichte; Welt